Police Brutality Terhadap Tersangka dalam Proses Pembuatan Berita Acara Pemeriksaan (BAP) Tindak Pidana - Iasha Perthiani; Monica Margaret (Universitas Budi Luhur, 2022)
The use of violence or torture in the course of investigations is prohibited in Indonesian laws and international conventions. Nevertheless, the phenomenon of abuse during the examination stage is still frequently encountered. This study discusses how the phenomena of acts of violence and torture were committed by law enforcers, in this case the Police, in the investigative process stage which will be analyzed using the conflict theory developed by Richard Quinney, namely The Social Reality Of Crime. The research uses descriptive qualitative method, with primary data in the form of interviews and secondary data through literature studies. This research found that the use of violence during the process of investigation or arrest is still acceptable within the Polri institution due to human nature which cannot be controlled. There are Polri members who use their powers in secret with the aim of intimidating suspects of criminal acts so that these persons can fulfill all their interests, from confessions, statements, to other administrative needs.